Pre-Diagnosis and Pre-Treatment Loss to Follow-Up Among Individuals with Presumptive Tuberculosis and Diabetes Mellitus: A Retrospective Study Using Routine Surveillance Data in Minahasa, North Sulawesi - Gordianus Lelang Wejak; Doni Anshar Nuari; Dika Pramita Destiani; Ivan Surya Pradipta (Jurnal Ilmiah Farmako Bahari, 2026)
Tuberculosis (TB) remains a foremost infectious cause of death worldwide and stands as a major public health concern, particularly in high-burden countries such as Indonesia. Loss to follow-up (LTFU) during the early stages of the TB care cascade, including diagnostic evaluation and treatment initiation, contributes to under-detection and ongoing transmission. Patients with diabetes mellitus (DM) are at increased risk of TB and poor outcomes, with evidence on early-stage LTFU in this population remaining limited in specific settings such as district-level health systems. The objective of this study is to assess the proportion of pre-diagnosis and pre-treatment LTFU and to explore associated factors among presumptive TB individuals with DM. A retrospective cross-sectional study was performed using secondary data from Sistem Informasi Tuberkulosis (SITB). The study population comprised presumptive TB individuals with DM aged ≥18 years recorded between January 1 and November 30, 2025. Total sampling was applied. The chi-square or Fisher’s exact test was employed for bivariate statistical analysis. A p-value <0.05 was considered statistically significant. A total of 289 presumptive TB individuals with DM were included. Pre-diagnosis LTFU was 4.8 %, while pre-treatment LTFU was 6.4 %. Pre-diagnosis LTFU was significantly associated with area of residence (p=0.021), mode of entry into the TB program (p<0.001), and HIV status (p=0.037), suggesting that disparities in healthcare access and clinical characteristics may influence completion of the diagnostic process. No significant associations were observed for pre-treatment LTFU, likely due to the very limited number of events. Early-stage attrition in the TB-DM care cascade remains low but critical (4.8% pre-diagnosis and 6.4% pre-treatment LTFU). Geographical factors, entry points, and HIV comorbidity significantly influence diagnostic continuity. Minimizing patient loss requires strengthening localized tracking, enhancing referral coordination, and optimizing TB-HIV integration within routine health systems.